Home Peers, Business Owners’ Gender, and the Export Intensity of SMEs - Sui, Sui; Morgan, Horatio M. (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
Small and medium-sized enterprises (SMEs) can improve their export performance by co-locating with export firms from the same industry and country. However, the export implications are yet to be addressed systematically. This study investigates when and how women-owned SMEs convert their geographic proximity to home peers through social proximity and cognitive proximity into high export intensity. We develop a nuanced knowledge spillover perspective incorporating gender mechanisms to clarify the relationship between home peers and SMEs’ export intensity at the regional and national levels. To test our hypotheses, we designed quantitative research using a survey database from Statistics Canada, Survey on Financing and Growth of Small and Medium Enterprises (SFGSME), with a sample of 9,977 Canadian SMEs. Our study shows that, among other things, home peers’ positive impact on SMEs’ export intensity is more significant when their owners are exposed to a larger number of relatively close same-gender home peers (i.e., same-gender regional home peers). Moreover, we show that such positive home-peer effects on SMEs’ export intensity are even stronger for women business owners than men business owners. We clarify our contributions by discussing the theoretical and practical implications of our findings. By demonstrating the significance of same-gender regional home peers for women owners, we contribute to the knowledge spillover perspective on exporting, emerging research streams on home peers, and women entrepreneurship research in the international entrepreneurship field. Our findings also suggest that women entrepreneurs can particularly benefit from government-funded export promotion programs when the programs are appropriately designed and promoted to women entrepreneurs.